Determination of the breeding value of collection chickpea (Cicer arietinum L.) accessions by cluster analysis - N. A. Vus; L. N. Kobyzeva; O. N. Bezuglaya (Вавиловский журнал генетики и селекции)
Assessment of the genetic resources of chickpea (Cicer arietinum L.) in a zone that is atypical for its cultivation (eastern forest-steppe of Ukraine) gives an opportunity to identify valuable starting material for priority breeding areas. The article presents the results of a cluster analysis on chickpea accessions from the National Center for Plant Genetic Resources of Ukraine (NCPGRU) for a set of agronomic characteristics. In 2005-2017, 653 chickpea accessions from the NCPGRU's core collection were studied: 369 kabuli accessions and 284 desi accessions. One hundred and fifty two sources of valuable traits were identified for 11 parameters: drought tolerance, resistance to Ascochyta leaf and pod spot, early ripening (vegetation period length), yield, performance, number of productive pods and seed number per plant, response to nitrogenization, protein content, seed size, and cooking quality. These accessions (77 kabuli accessions are light-colored and 75 desi ones are dark-colored) were grouped by a set of valuable economic characteristics using cluster analysis with the Euclidean distance as a measure. The study showed that this sample consisted of 4 clusters. Cluster 1 contained mainly kabuli accessions with optimal combinations of valuable traits: drought tolerance, resistance to Ascochyta leaf and pod spot, large seeds, high yield capacity and performance, pod and seed numbers as well as protein content in seeds. This cluster includes standards and most of reference varieties, which are well-adapted to the conditions of the eastern forest-steppe of Ukraine. The accessions of cluster 2 are characterized by high resistance to Ascochyta leaf and pod spot, late ripening, small seeds, low protein content, moderate response to nitrogenization, high performance attributed to a large number of productive pods and seeds per plant. Most of the accessions of this cluster are small-seeded late-ripening kabuli accessions. Cluster 3 consists of 3 accessions, which have large seeds and high protein content in them, give moderate yields, are highly responsive to nitrogenization and poorly resistant to Ascochyta leaf and pod spot. Cluster 4 comprises mainly desi accessions (63 %), which are mid-ripening, with small seeds, low performance, moderate yield capacity, medium protein content, poor cooking quality, moderate resistance to Ascochyta leaf and pod spot, and low drought tolerance. Representatives of this cluster are predominantly sources of one trait and may have restricted application in specialized breeding programs. Based on the data obtained, we concluded that the accessions of cluster 1 were preferable in breeding programs to develop chickpea varieties for the forest-steppe zone.